2018
DOI: 10.1080/13880209.2018.1424209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Danshen tablets on pharmacokinetics of atorvastatin calcium in rats and its potential mechanism

Abstract: Context: Danshen tablets (DST), an effective traditional Chinese multi-herbal formula, are often combined with atorvastatin calcium (AC) for treating coronary heart disease in the clinic.Objective: This study investigated the effects of DST on the pharmacokinetics of AC and the potential mechanism.Materials and methods: The pharmacokinetics of AC (1 mg/kg) with or without pretreatment of DST (100 mg/kg) were investigated using LC-MS/MS. The effects of DST (50 μg/mL) on the metabolic stability of AC were also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous studies (Sun et al. 2018) have also reported that drugs or herbs could affect the pharmacokinetics of AC through affecting the activity of CYP3A4 enzyme.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies (Sun et al. 2018) have also reported that drugs or herbs could affect the pharmacokinetics of AC through affecting the activity of CYP3A4 enzyme.…”
Section: Discussionmentioning
confidence: 98%
“…2016; Sun et al. 2018). Group B was pre-treated with GLT solutions by oral gavage at a dose of 80 mg/kg/day for 10 days before the administration of AC, and then AC were orally administered to rats by oral gavage at a dose of 1 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear change was observed in the AUC 0 -60h and AUC 0-∞ between the different formulae. In ATV-SD tablets the mean AUC (0-60) was found to increased from 63.54 ng.hr/ ml to 92.35 ng.h/ml, in addition the AUC(0-∞) was increased from 65.40 ng.hr/ ml to 95.73 ng.hr/ml , which indicated that the pharmacological activities of ATV may be increased 24 . The mean elimination half-life (T1/2) and elimination rate constant (K) were 4.68 hr and 0.15hr -1 , respectively in ATV-SD tablets .…”
Section: In Vivo Studymentioning
confidence: 91%
“…It has been widely applied clinically in the treatment of obstructive cerebrovascular diseases [21], atherosclerosis [22], coronary heart disease [23], and other cardiovascular diseases [24,25]. Furthermore, many different preparations of S. miltiorrhiza can be found, including compounded danshen dripping pills [26], danhong injection [27], danshen injection [28], danshen tablets [29], and danshen granules [30]. Moreover, S. miltiorrhiza extract is a high-value raw pharmaceutical material commonly used in Chinese patented medicine production.…”
Section: Introductionmentioning
confidence: 99%